SIKAP KEWIRAUSAHAAN DAN PENGARUHNYA TERHADAP PERKEMBANGAN USAHA KERAJINAN BATIK DI TASIKMALAYA - Mira Nurfitriya (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
The problem in this research is business development in the form of profit of batik entrepreneurs in batik center of Tasikmalaya city that fluctuated up and down in the last 5 months. This is due to the lack of positive mental attitudes of batik entrepreneurs in the form of entrepreneurial attitudes such as confidence, task-oriented attitude and outcome, risk-taking attitude, leadership attitude, future-oriented attitude, and the attitude of originality (creativity and innovation) to improve its business development. In this study, the object of research is the batik entrepreneurs in the center of batik handicrafts Tasikmalaya city. The sample in this research were 31 people taken with saturated sampling technique. The method used in this research is explanatory survey using questionnaire as data collecting tool and technique using simple linear regression, in data analysis using SPSS 11.5 for Windows program. Based on the result of the research, it is found that partially variable of entrepreneurship attitude has a positive and significant effect on business development. From the research results also obtained R2 value of 74.1% which shows that the influence of entrepreneurial attitude toward business development is equal to 74.1%, meaning 74.1% change in the profit of batik entrepreneurs in the center of batik handicrafts Tasikmalaya city influenced by entrepreneurial attitude and the rest 25.9 % influenced by other factorsDOI: https://dx.doi.org/10.17977/UM014v11i12018p001